Synthesis of Novel 1,2,4-Triazole Derivatives as Antimicrobial Agents via the Japp-Klingemann Reaction: Investigation of Antimicrobial Activities - Tasneem Taj; Ravindra R. Kamble; Atukuri Dorababu; Gangadhar Y. Meti (Journal of Chemistry)
In the present investigation, 1,2,4-triazole appended to pyrazoline and pyrazole rings (4a–g) using N-arylsydnone as synthon was prepared. The title compounds were subjected to Osiris property explorer for the oral bioavailability to analyze their drug likeness and drug score. Further, the compounds were subjected to the antimicrobial activity and analyzed the IC 50 and MIC values.